2017
DOI: 10.4236/ce.2017.81001
|View full text |Cite
|
Sign up to set email alerts
|

Developing Gifted and Talented Education Program: The Malaysian Experience

Abstract: The Malaysian Education Act 550 (1996) outlines six dimensions of national education system namely, the pre-school, elementary, secondary, post-secondary, higher, and special education. Thus, the other paradigms of education; for instance, gifted education, are not considered as mainstreams and do not give considerable attention towards their holistic growth. Even though initiatives to cater for the needs of local population of gifted students or students with high potentials were in existence since the 1960s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, (Bakar, 2017) The strategies needed to improve the quality of the gifted and talented students in secondary schools.…”
Section: Challenges Faced the Gifted And Talented Studentsmentioning
confidence: 99%
“…Furthermore, (Bakar, 2017) The strategies needed to improve the quality of the gifted and talented students in secondary schools.…”
Section: Challenges Faced the Gifted And Talented Studentsmentioning
confidence: 99%
“…The gifted and talented group of individuals have proven their role in the success of the country as seen in many developed countries such as the U.K. and the U.S. (Zakaria et al, 2021;2017;Bakar & Zakaria, 2023;Ishak, & Bakar, 2017).…”
Section: Why Gifted Studentsmentioning
confidence: 99%
“…With a proper plan and supervision from the teachers', gifted students are expected to develop and enhance their potentials over a period of time they spend in the special program (Beecher & Sweeny, 2008;Renzulli, 1999;Kulik & Kulik, 1992). Researches have shown that gifted students could learn at a much faster rate, earlier than their peers, have better memories, think abstractly, focus intensely, absorb many stimuli, have stronger empathy and high moral concern (Renzulli & Reis, 1997;VanTassel-Baska, 1992;Gagne, 2005;Bakar, 2017;Ishak & Bakar, 2017). There is no such thing as one size fits all concept in teaching the gifted students because of the uniqueness in their way of thinking and studying a particular subject matter.…”
Section: Giftedness and Educationmentioning
confidence: 99%
“…A specialized curriculum for gifted students is therefore fundamental. Compared to their peers, gifted students have special social and emotional needs (Phelan & Allen, 2018;Bakar, 2017;Cavilla, 2016). The schools need to know how to facilitate better performance for each student which can be a challenging task, particularly in classrooms where there are several levels of ability.…”
Section: Curriculum Materials For Gifted Students (Cmgs)mentioning
confidence: 99%